Thermoluminescence (TL) kinetics of CaSO4 and LiF standard materials: a comparative study - Deshpande, A S; Dhoble, N S; Gedam, S C; Dhoble, S J (Recent Research in Science and Technology, 2012)
In this paper we present comparative reports on CaSO4 and LiF standard materials. CaSO4: Mn has a very high sensitivity but fading of the dosimetry peaks is relatively rapid. The CaSO4: Tm and CaSO4: Dy each has a stable glow peak at about 220°C. LiF has an effective Z of 8.2 (of. 7.4 for tissue) and the energy response relative to tissue is good. Both the materials are available commercially.